High-throughput sequencing reveals the presence of novel and known viruses in diseased Paris yunnanensis - Lan, Ping-xiu; He, Peng; Yang, Jie; Zhou, Guo-hua; Chen, Xiao-jiao; Wei, Tai-yun; Li, Chen-rong; Gu, Rong; Li, Ruhui; Li, Fan (Frontiers in Microbiology, 2022)
Viral diseases of Paris spp. have become serious problems in cultivation of this group of important medicinal plants in China. In this study, eight viruses were identified in the diseased plants of Paris yunnanensis by high-throughput sequencing (HTS) and RT-PCR. These viruses include three novel viruses (two potyviruses and one nepovirus), Hippeastrum chlorotic ringspot virus (HCRV)，Lychnis mottle virus (LycMoV), Paris mosaic necrosis virus (PMNV), Paris virus 1 and pepper mild mottle virus. The three new viruses were tentatively named Paris potyvirus 3 (ParPV-3), Paris potyvirus 4 (ParPV-4), Paris nepovirus 1 (ParNV-1) and their complete genome sequences were determined. Sequence analyses showed ParPV-3 and ParPV-4 shared the highest amino acid (aa) sequence identities of 54.3% to each other and 53.0-57.8% to other known potyviruses. ParNV-1 had aa sequence identities of 28.8-63.7% at protease-polymerase (Pro-Pol) with other nepoviruses. Phylogenetic analyses further support that the three viruses are new members of their corresponding genera. Analyses of the partial sequences of HCRV and LycMoV infecting P. yunnanensis revealed they diverged from existing isolates by aa sequence identities of 97.1% at glycoprotein precursor of HCRV and 93.3% at polyprotein of LycMoV. These two viruses are reported for the first time in Paris spp. A total of 123 field samples collected from P. yunnanensis in four counties of Yunnan, Southwest China were tested by RT-PCR for detecting each of the eight viruses. Results showed that nearly half of the samples were positive for at least one of the eight viruses. Two potyviruses, ParPV-3 (26.8%) and PMNV (24.4%), were predominant and widely distributed in the fields, while other viruses occurred in low rates and/or had limited distribution. This study insights into the virome infecting P. yunnanensis and provides valuable information for diagnosis and control of viral diseases in P. yunnanensis.